Manajemen Komunikasi Pelayanan Jasa Tour Dan Travel Manca Negara di PT. Zafa Mulia Mandiri Wilayah Bengkulu - Apriadi Apriadi; Yanto Yanto; Anis Endang Sri Murwani (UNIVED PRESS, Universitas Dehasen Bengkulu, 2023)
The purpose of this study is to describe or find out how PT Zafa Mulia Mandiri Bengkulu Region manages communication in order to serve consumers during departure delays and after being allowed to return to depart for Umrah. This study uses a qualitative approach with a case study type of research. This research focuses intensively on a particular object that is studied as a case. Data collection techniques in this study were (1) interviews, (2) observation, and (3) documentation. Data analysis techniques in this study were (1) data reduction, (2) data presentation, and (3) verification/conclusion. The results of the study show that (1) the company determines the criteria for consumers who are healthy and have financial ability, (2) the company prioritizes service to consumers, (3) the company conducts interviews during registration to find out current conditions, (4) the company provided services before the pandemic, during a pandemic, and after a pandemic in accordance with applicable regulations, (5) the company informs about delays in departure, due to current conditions, (6) when it is permitted to return pilgrims, in terms of service, the company prioritizes consumers whose departure is delayed, and (7 ) The company is moving quickly in response to the current situation, namely by dispatching pilgrims as soon as permission to depart has been obtained. The research results are based on the Management by Objectives (MBO) concept which includes: (1) understanding the desired goals, (2) finding facts about current conditions, (3) comparing the desired goals with existing facts, (4) looking for causes of problems, (5) having alternative solutions to problem solving, (6) alternative decisions by setting decision criteria, and (7) making decisions that have been determined.